COMPREHENSIVE REVIEW OF RADIOLOGICAL PROTOCOLS IN PREHOSPITAL CARE IN ASSESSING IMAGING MODALITIES, RADIATION SAFETY, AND PROTOCOL ADHERENCE - ABDULLAH SAMIR ABU AL-SAFA, MAJED BADER ALMUTAIRI, AFRAH HAMDAN ALMUTAIRI, HAMED BADER M ALMUTAIRI, MAZEN JAZI ALHUMIREEN, MARIAM ADAL ALENAZI (Chelonian Research Foundation, 2022)
Radiological tools are irreplaceable in prehospital care, are indispensable for immediate diagnosis, and efficiently control illnesses and injuries. This comprehensive appraisal looks at 'pipeline screening protocols' in prehospital settings using imaging modalities, radiation safety measures, and protocol adherence as its key focus areas. Underpinning this review with the literature review findings, evidence, and statistics extends to the significance of both strong and weak points of the present practices. Fellow, the guide includes a set of recommendations to foster radiological protocols that work towards the best possible care and safety of patients within the prehospital environment. Healthcare institutions can rise to the challenge of developing high-quality and objective radiological protocols by actively taking on three selected elements, namely protocol standardization, radiation safety training, and communication, to improve overall patient care and protect the health of patients and healthcare workers. Keywords: radiological protocols, prehospital care, imaging modalities, radiation protection, compliance with protocols.